Polar Mesospheric Summer Echo Characteristics in Magnetic Local Time and Height Profiles - Young-Sook Lee; Ram Singh; Geonhwa Jee; Young-Sil Kwak; Yong Ha Kim (Journal of Astronomy and Space Sciences, 2023)
We conducted a statistical study of polar mesospheric summer echoes (PMSEs) in relation to magnetic local time (MLT), considering the geomagnetic conditions using the K-index (or K). Additionally, we performed a case study to examine the velocity profile, specifically for high velocities (≥ ~100 m/s) varying with high temporal resolution at high K-index values. This study utilized the PMSE data obtained from the mesosphere–stratosphere–troposphere radar located in Esrange, Sweden (63.7°N, 21°E). The change in K-index in terms of MLT was high (K ≥ 4) from 23 to 04 MLT, estimated for the time PMSE was present. During the near-midnight period (0–4 MLT), both PMSE occurrence and signal-to-noise ratio (SNR) displayed an asymmetric structure with upper curves for K ≥ 3 and lower curves for K < 3. Furthermore, the occurrence of high velocities peaked at 3–4 MLT for K ≥ 3. From case studies focusing on the 0–3 MLT period, we observed persistent eastward-biased high velocities (≥ 200 m/s) prevailing for ~18 min. These high velocities were accompanied with the systematic motion of profiles at 85–88 km, including large shear formation. Importantly, the rapid variations observed in velocity could not be attributed to neutral wind effects. The present findings suggest a strong substorm influence on PMSE, especially in the midnight and early dawn sectors. The large zonal drift observed in PMSE were potentially energized by local electromagnetic fields or the global convection field induced by the electron precipitation during substorms.